HIGH MOLECULAR WEIGHT HYALURONIC ACID FOR ENHANCING EPITHELIAL SURVIVAL AND RECONSTITUTION OF BODY SURFACES - VAN SETTEN GYSBERT-BOTHO; MULLER-LIERHEIM WOLFGANGGEORG KONRAD (2021)
The invention concerns a method for restoring or replenishing hyaluronic acid at an epithelial surface of a subject, the method comprising topically administering a composition to the epithelial surface of the subject, wherein the composition comprises high molecular weight hyaluronic acid, high molecular weight hyaluronic acid analogue, or a combination thereof, and the epithelial surface has a deficiency in the amount or function of hyaluronic acid. 本发明涉及一种用于在受试者的上皮表面上恢复或补充透明质酸的方法，其包括将组合物局部施用于受试者的上皮表面，其中所述组合物包含高分子量透明质酸，高分子量透明质酸类似物或它们的组合，并且其中上皮表面的透明质酸的量或功能不足。